Regulatory principles governing Salmonella and Yersinia virulence - Erhardt, Marc; Dersch, Petra (Frontiers in Microbiology, 2015)
Enteric pathogens such as Salmonella and Yersinia evolved numerous strategies to survive and proliferate in different environmental reservoirs and mammalian hosts. Deciphering common and pathogen-specific principles for how these bacteria adjust and coordinate spatiotemporal expression of virulence determinants, stress adaptation and metabolic functions is fundamental to understand microbial pathogenesis. In order to manage sudden environmental changes, attacks by the host immune systems and microbial competition, the pathogens employ a plethora of transcriptional and post-transcriptional control elements, including transcription factors, sensory and regulatory RNAs, RNAses and proteases, to fine-tune and control complex gene regulatory networks. Many of the contributing global regulators and the molecular mechanisms of regulation are frequently conserved between Yersinia and Salmonella. However, the interplay, arrangement and composition of the control elements vary between these closely related enteric pathogens, which bring out phenotypic differences leading to distinct pathogenic properties. In this overview we present common and different regulatory networks used by Salmonella and Yersinia to coordinate the expression of crucial motility, cell adhesion and invasion determinants, immune defense strategies, and metabolic adaptation processes. We highlight evolutionary changes of the gene regulatory circuits that result in different properties of the regulatory elements and how this influences the overall outcome of the infection process.